Imputación penal de los menores: análisis y debate sobre la responsabilidad individual frente a la protección del menor. - Alvarado Gaona, Camila Elizabeth (2024)
This research addresses the fundamental problem of contemporary juvenile criminal justice: the tension between the social need to hold juvenile offenders accountable and the legal-moral duty to protect their fundamental rights and guarantee their integral development. This multidimensional study examines the various aspects that converge in this complex legal and social reality. The criminal charge of minors is a subject that has given rise to intense debate in the legal and social sphere. This research analyzes the tension between the individual responsibility of minors and the need to protect their development and well-being. It examines the existing legal frameworks in different jurisdictions, as well as theories on criminal responsibility and the protection of children's rights. The implications of considering minors as subjects of law are discussed, confronting their criminal responsibility with the idea of rehabilitation and social reintegration. Through a critical analysis of case studies and statistics, we seek to offer a balanced view that contemplates both the need for justice and the protection of the juvenile, proposing possible reforms that guarantee a more humane and effective approach.